Sustainable Development and Investment of Waqf Assets from the Islamic Perspective - Sulaiman, Syahnaz; Hasan, Aznan; Sulaiman @ Mohamad, Ahmad Azam (Kanun: Jurnal Undang-undang Malaysia, 2016)
The initiative towards enhancing the role of waqf (endowment) as the main driving force for socioeconomic development of the ummah has received tremendous support from the Muslim community globally. Considerable attention has been paid to the aspect of waqf development and investment in order to maintain the sustainability of waqf assets to meet their divine and worldly objectives. Various mechanisms for waqf development, whether theoretical or already implemented, have intensified the effort to improve and raise the status of waqf assets not only in Malaysia but also throughout the world. Essentially, this study will discuss the concept of sustainable development and investment of waqf assets in the light of the Shariah. This study renders general guidelines towards implementing viable approaches for the development and investment of waqf assets that are in line with Islamic teachings and laws in Malaysia. Keywords: waqf, development, investment